Theoretical foundations of functional data analysis, with an introduction to linear operators - Hsing, Tailen, 1955- (Wiley, 2015)
Provides essential coverage of functional data analysis and related areas. This book provides a uniquely broad compendium of the key mathematical concepts and results that are relevant for the theoretical development of functional data analysis (FDA). The self-contained treatment of selected topics of functional analysis and operator theory includes reproducing kernel Hilbert spaces, singular value decomposition of compact operators on Hilbert spaces and perturbation theory for both self-adjoint and non self-adjoint operators. The probabilistic foundation for FDA is described from the perspecti.